A matched model-based synthetic aperture focusing technique for acoustic microscopy. (June 2019) - Wuest, Michael; Schwarz, Michael; Eisenhart, Johannes; Nierla, Michael; Rupitsch, Stefan J.
Abstract: This contribution deals with an advanced synthetic aperture focusing technique for acoustic microscopy, which enables an almost precise reconstruction of the reflectivity distribution of both fluid-like and solid specimen. The presented approach is designed for single-element ultrasonic immersion transducers as they are commonly used in scanning acoustic microscopes. In practice, the resulting images offer at least lateral and axial resolutions of a focused image, which was acquired by a transducer with double center frequency. Moreover, the results show very low side lobe levels and the approach reconstructs the shape of inner defects even in images with present multiple reflections. A comparison with the well-known delay-and-sum technique reveals that the introduced approach offers a significantly more precise reconstruction of the given reflectivity distribution, especially when a complex reflectivity distribution is investigated. The advanced synthetic aperture focusing technique is applied to a generic test samples and to a curved multi-layered compound specimen.